Nilai-nilai fleksibiliti dalam sumber perundangan islam - Wan Zulkifli Wan Hassan, (Universiti Kebangsaan Malaysia, 2009)
The aim of this paper is to highlight the values of flexibility in the Islamic sources of law. This is to prove that Islamic laws are not static and irresponsive of changes in the contemporary society, rather it is relevant to be adopted into all aspects of life across different places and periods of time. The primary sources of Islamic jurisprudence as accepted by all Muslim jurists are the al- Qur’an and hadith as well as ijtihad or consensus of the fuqaha’ (jurists) and al-qiyas (analogical deduction). Some jurists also include other sources of law such as al-istihsan (equity), al-masalih al-mursalah (considerations of public interest), al-’urf (customs), al-istishab (presumption of continuity) and al-dhara’i (blocking the means). Taken together, all these laws complete each other and thus able to guide Muslims to choose the best course of action to solve their problems